Вивчення укріплень Поділля XIII—XVIII ст. (за археологічними даними) - Виногродська, Л.І. (Археологія і давня історія України, 2010)
У статті розглядаються замки Поділля, що
досліджувалися автором. Подається їх хронологія
і коротка характеристика фортифікації і матеріальної культури, що відповідає хронологічним
періодам історії будівництва замків на Поділлі. В статье рассматриваются некоторые укрепления
Подолии, которые исследовались автором. Укрепления Подолии развитого средневековья (ХІІІ—ХV вв.) и раннего нового времени (ХVІ—ХVІІ вв.) до сегодняшнего дня недостаточно изучаются археологами, хотя именно археологические исследования
играют значительную роль в определении хронологии памятников и их исторического развития во
времени. Рассмотренные в статье фортификации по
археологическим данным существуют беспрерывно
на территории замков в Брацлаве, Зинькове, Пиляве, Виннице, Каменец-Подольском и, по нашему
мнению, на большинстве других замков достаточно долгое время — от древнерусского времени до конца
ХVІІІ в. Это указывает на традиции строительства укреплений средневекового и нового времени на древнерусских мысовых городищах, которые, в свою очередь, сооружались на поселениях более ранних периодов. Анализ материальной культуры говорит
о военном образе жизни на территории замков в ХІІІ—ХV вв., который постепенно, по мере уменьшения военной опасности, сменяется на светский в ХVІ—ХVІІІ вв., что целиком отвечает движению колонизационного процесса на Правобережье Украины и государственной политике Речи Посполитой. The paper proposes some investigations results
about fortifications in Podillya of 13th—17th cent.
These monuments were studied by the author. Fortresses
of Podillya still are not enough investigated by
archaeologists. In spite of the fact, that archaeological
researches mainly could propose a solution to the
problems of chronology and historical development of
monuments.
According to archaeological artifacts fortifications of
fortresses on the territory of Podillya were exist without
a break from Old Russ period to the end of 17th cent.
Author notices this tendency for fortresses of Bratslav,
Zinkiv, Pylyava, Vinnytsya, Kamjanets-Podilskyj and
many other fortresses at the author’s opinion. This fact
indicates tradition of building up on places where Old
Russ sites were located. Old Russ fortresses in its turn
were located on places of earlier settlements. Analysis
of material culture shows that a way of life in 13th —
15th cent. in these fortresses had military direction.
As time goes by a way of life becomes more peaceful in
16th — 18th cent. This tendency is in general agreement
with processes of colonization the territory of
Ukraine at the right bank of Dnipro and with a state
policy of Rich Pospolyta.